The Effect of Gamification in Learning English for Non Language Majority Class at University Level: Solomon Study - Aryawira Pratama; Hadiyanto; Eddy Haryanto; Bunga Ayu Wulandari (Yayasan Nurul Yakin Bunga Tanjung, 2026)
Gamification is increasingly used in higher education to enhance student motivation, engagement, and learning outcomes. However, its impact on specific English skills for non-language majors, particularly in STEM, remains under-researched, especially considering pre-test sensitization effects. This study examines the effect of Kahoot!-based gamification on English grammar, reading comprehension, and vocabulary acquisition among mathematics education students. A Solomon Three-Group design was employed: Group 1 (experimental) – pretest, treatment, posttest; Group 2 (control 1) – pretest, no treatment, posttest; Group 3 (control 2) – no pretest, treatment, posttest. Data were collected via pre- and post-tests, with analysis using paired-sample t-tests for within-group changes and ANOVA for between-group comparisons. Results showed significant improvement in the experimental group (p = 0.008). ANOVA indicated no significant difference between the experimental and control 1 groups, but significant differences emerged between the experimental and control 2 groups, as well as between the two control groups, highlighting the influence of pre-testing on gamification effectiveness. Cohen’s d = 0.42 suggests a modest effect. Overall, the study provides evidence that gamification can enhance English learning outcomes among non-language majors, particularly when combined with initial assessment to guide targeted interventions.